Derivation of a Human In Vivo Benchmark Dose for Perfluorooctanoic Acid From ToxCast In Vitro Concentration–Response Data Using a Computational Workflow for Probabilistic Quantitative In Vitro to In Vivo Extrapolation - Loizou, George; McNally, Kevin; Dorne, Jean-Lou C. M.; Hogg, Alex (Frontiers in Pharmacology, 2021)
A computational workflow which integrates physiologically based kinetic (PBK) modelling; global sensitivity analysis (GSA), Approximate Bayesian Computation (ABC) and Markov Chain Monte Carlo (MCMC) simulation was developed to facilitate quantitative in vitro to in vivo extrapolation (QIVIVE). The workflow accounts for parameter and model uncertainty within a computationally efficient framework. The workflow was tested using a human PBK model for perfluorooctanoic acid (PFOA) and high throughput screening (HTS) in vitro concentration-response data, determined in a human liver cell line, from the Toxcast/Tox21 database. In vivo benchmark doses (BMD) for PFOA intake (ng/kg BW/day) and drinking water exposure concentrations (µg/L) were calculated from the in vivo dose-responses and compared to intake values derived by the European Food Safety Authority (EFSA). The intake Benchmark Dose Lower confidence limit (BMDL5) of 0.82 was similar to 0.86 ng/kg BW/day for altered serum cholesterol levels derived by EFSA whereas the intake BMDL5 of 6.88 was six-fold higher than the value of 1.14 ng/kg BW/day for altered antibody titre also derived by EFSA. Application of a chemical specific adjustment factor (CSAF) of 1.4, allowing for inter-individual variability in kinetics, based on biological half-life, gave an intake BMDL5 of 0.59 for serum cholesterol and 4.91 (ng/kg BW/day), for decreased antibody titre, which were 0.69 and 4.31the EFSA derived values, respectively. The corresponding BMDL5 for drinking water concentrations, for oestrogen receptor binding activation associated with breast cancer, pregnane X receptor binding associated with altered serum cholesterol levels, thyroid hormone receptor α binding leading to thyroid disease and decreased antibody titre (pro-inflammation from cytokines) were 0.883, 0.139, 0.086 and 0.295 ng/mL, respectively with application of no uncertainty factors. These concentrations are; 5.7, 36, 58.5 and 16.9 fold lower than the median measured drinking water level for the general US population which is approximately, 5ng/mL.